Great Illustrated Classics/ The Swiss family Robinson - Wyss, Johann David, 1743-1818.; Warren, Eliza Gatewood; Pablo Marcos Studio (New York, NY : Baronet Books, 1989)
Relates the fortunes of a shipwrecked family as they imaginatively adapt to life on an island with abundant animal and plant life.
Keywords: Survival -- Fiction; Families -- Fiction